PENGEMBANGAN MEDIA PEMBELAJARAN MODUL PADA MATA DIKLAT PENGUKURAN DI SMK - Haris Abizar (Jurnal Taman Vokasi, 2015)
The aims of this research were: (1) to make module for subject direct measurement; (2) to evaluate the feasibility of module the subject direct measurement; (3) to measures the effect of the implementation of the module for subject direct measurement to the learning achievements of grade X students of machine engineering department of SMK N 2 Depok, Sleman. This research was based on research development Borg & Gall (1989) with use 9 steps. This research implemented in SMK N 2 Depok, Sleman of grade X-A and X-B. Data collection techniques used that field observations, questionnaires, and tests. Research instrument used that field observations sheet, questionnaires sheet, and question sheet. Analysis data used qualitatively and quantitatively. The results showed: (1) Media module is made to have the characteristics of an effective , easy to understand , and systematic; (2)Â  media assessment module were feasible for use with an average overall category of "good"; and (3) learning outcomes were the post-test value of X- B ( score 83.37 ) is better than X- B ( score 79.03 ) so learning to used media module can improve learning achievement.